Transcriptome analysis of host-associated differentiation in Bemisia tabaci (Hemiptera: Aleyrodidae) - Xie, Wen; Wu, Qingjun; Wang, Shaoli; Jiao, Xiaoguo; Guo, Litao; Zhou, Xuguo; Zhang, Youjun (Frontiers in Physiology, 2014)
Host-associated differentiation is one of the driving forces behind the diversification of phytophagous insects. In this study, host induced transcriptomic differences were investigated in the sweetpotato whitefly Bemisia tabaci, an invasive agricultural pest worldwide. Comparative transcriptomic analyses using coding sequence (CDS), 5’ and 3’ untranslated regions (UTR) showed that sequence divergences between the original host plant, cabbage, and the derived hosts, including cotton, cucumber and tomato, were 0.11%-0.14%, 0.19%-0.26% and 0.15%-0.21%, respectively. In comparison to the derived hosts, 418 female and 303 male transcripts, respectively, were up-regulated in the original cabbage strain. Among them, 17 transcripts were consistently up-regulated in both female and male whiteflies originated from the cabbage host. Specifically, two ESTs annotated as Cathepsin B or Cathepsin B-like genes were significantly up-regulated in the original cabbage strain, representing a transcriptomic response to the dietary challenges imposed by the host shifting. Results from our transcriptome analysis, in conjunction with previous reports documenting the minor changes in their reproductive capacity, insecticide susceptibility, symbiotic composition and feeding behavior, suggest that the impact of host-associated differentiation in whiteflies is limited. Furthermore, it is unlikely the major factor contributing to their rapid range expansion/invasiveness.